Inventory management and payment system using RFID as a medium - Faiz Misuari, Mohamad Ali (2012)
This thesis deal with developing inventory management and payment system using RFID as a medium of data transfer. Every retail outlet such as supermarket and shop worldwide has their own inventory management and payment system.It is important that both of the system work together to ensure precise and accurate item flow in and out and to ensure no mistake in payment process and in inventory management. Traditional inventory system and payment system using price tag and barcode usually fail to integrate together to deliver up-to-date inventory and also slow down the payment process.To overcome this,Automatic Identification and Data Capture (AIDC) or Automatic Identification and Mobility (AIM) technology is chosen to be used as a medium of data exchange.Radio Frequency Identification (RFID) is chosen to get precise and up-to-date inventory information and ensures faster payment process.This method overcomes the problem of manually calculating the inventory,manually key-in price for price tag and also overcome the process of scanning barcode tag.Therefore,experience or inexperience employee could use this system.Last but not least,customer would automatically be involved in using this system without the need to undergo any training.